International legal status of “unrecognized states” as special political and territorial entities - A. V. Voitsikhovskyi; M. I. Marchuk; Y. S. Logvynenko (Law and Safety)
Problems of determining the status of so-called unrecognized states in terms of modern international law are revealed. It is noted that the desire of different territorial entities to secede in recent years increasingly leads to the emergence of “unrecognized states” as special political and territorial entities, whose existence is one of the sources of conflict in modern world politics. Many works by both domestic and foreign scholars are devoted to the problems of determining the international legal status of “unrecognized states” and their domestic political development. However, a significant disadvantage of these scientific works is that their authors do not seek to develop general theoretical methodological approaches to the study of the phenomenon of “unrecognized states” and to determine the criteria of insolvency and non-recognition. It is noted that the study of the international legal status of self-proclaimed “unrecognized states” requires theoretical and methodological understanding, which is possible with a comprehensive scientific approach to this topic. Thus, in the current conditions of development of international relations, scholars in the field of international law, international relations and political science are faced with the task of finding optimal methodological and theoretical approaches to the study of the phenomenon of “unrecognized states”. An integrated approach to its study will help to determine the features of their domestic political development, to identify the relationship between the main trends in their formation and international legal status. The results obtained will determine the prospects for the recognition of such political and territorial entities (“unrecognized states”) with a special status and the development of their capacity. The purpose of the article is to define the term “unrecognized states”, to conduct a scientific and theoretical analysis of its content and consider the existing preconditions for its formulation, as well as to clarify the place of such political and territorial entities (“unrecognized states”) in international law. The objective of the article is to clarify the substantive characteristics of the term “unrecognized states”, the international legal status of such entities and analyze the principle of the right of peoples to self-determination and the principle of territorial integrity in the context of the emergence and existence of “unrecognized states”. The conflict in modern international law between the principle of the right of peoples to self-determination and the principle of territorial integrity, which are a prerequisite for geopolitical disputes in the current conditions of international relations is shown. Given the complexity of the practice of recognizing such entities, it was noted the need to develop clear legal norms that would regulate the procedure for the formation of such political and territorial entities (“unrecognized states”) as subjects of international law.